Getting the fundamentals right: assisting patients with eating and drinking. (2nd October 2019) - Semerdzhieva, Elizabeth; Reid, Bernie
Abstract : Compassion and effective communication are widely regarded as essential elements of quality person-centred nursing care, but these can be difficult to demonstrate during mealtimes. Elizabeth Semerdzhieva and Bernie Reid discuss the best techniques and approaches